Database taxonomics as key to modern plant biology - Koch, Marcus; German, Dmitry; Kiefer, Markus; Franzke, Andreas (Trends in plant science, 2018)
The advent of omic technologies opened new and multiple avenues to access higher levels of complexity. Taxonomy - discovering and naming biodiversity - has also entered a taxonomics epoch and serves as a tool not only to name biological diversity, but also to fully explore biological knowledge and to build bridges between disciplines.
Available online 13 November 2017
Gesehen am 24.10.2018